2016
DOI: 10.1038/srep38643
|View full text |Cite
|
Sign up to set email alerts
|

Contrast-enhanced transrectal ultrasound for prediction of prostate cancer aggressiveness: The role of normal peripheral zone time-intensity curves

Abstract: To assess the role of time-intensity curves (TICs) of the normal peripheral zone (PZ) in the identification of biopsy-proven prostate nodules using contrast-enhanced transrectal ultrasound (CETRUS). This study included 132 patients with 134 prostate PZ nodules. Arrival time (AT), peak intensity (PI), mean transit time (MTT), area under the curve (AUC), time from peak to one half (TPH), wash in slope (WIS) and time to peak (TTP) were analyzed using multivariate linear logistic regression and receiver operating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 26 publications
1
13
0
Order By: Relevance
“…Previous studies have shown that angiogenesis correlates with tumor recurrence following a radical prostatectomy [26][27][28]. Contrast-enhanced ultrasonography, which is useful for assessing microvessel density, has also been reported to have potential value in predicting the outcome of patients with prostate cancer [29,30]. Our study demonstrated that CETRUS scores may be a reliable predictor of biochemical recurrence following a radical prostatectomy in patients with localized prostate cancer.…”
Section: Discussionsupporting
confidence: 53%
“…Previous studies have shown that angiogenesis correlates with tumor recurrence following a radical prostatectomy [26][27][28]. Contrast-enhanced ultrasonography, which is useful for assessing microvessel density, has also been reported to have potential value in predicting the outcome of patients with prostate cancer [29,30]. Our study demonstrated that CETRUS scores may be a reliable predictor of biochemical recurrence following a radical prostatectomy in patients with localized prostate cancer.…”
Section: Discussionsupporting
confidence: 53%
“…Contrast-enhanced US can reflect tissue microvascular perfusion dynamically, which is a promising tool in the detection of PCa 22,23 and the prediction of the PCa risk. 24 In our study, we found that a combination of synchronous wash-in/out and equal enhancement on CEUS images with a homogeneous distribution indicated a benign lesion that differed from PCa.…”
Section: Discussionmentioning
confidence: 99%
“…Contrast‐enhanced TRUS has been used for diagnosis of prostate cancer in treatment‐naïve prostate glands with encouraging early outcomes . However, reports of contrast‐enhanced TRUS for evaluation of the prostate after HIFU are limited.…”
Section: Discussionmentioning
confidence: 99%
“…15 Contrast-enhanced TRUS has been used for diagnosis of prostate cancer in treatment-naïve prostate glands with encouraging early outcomes. 4 However, reports of contrast-enhanced TRUS for evaluation of the prostate after HIFU are limited. One study evaluated contrast-enhanced TRUS after whole-gland HIFU ablation during a short follow-up period of 1.5 months.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation